Impacts of long-term organic production on soil fauna in boreal dairy and cereal farming - Hagner Marleena; Pohjanlehto Ida; Nuutinen Visa; Setälä Heikki; Velmala Sannakajsa; Vesterinen Eero; Pennanen Taina; Lemola Riitta; Peltoniemi Krista (Elsevier B.V., 2025)
Intensified arable farming results in fewer functional groups of soil biota with decreased biodiversity. Organic farming with slurry fertilization and long crop rotation cycles favors soil fauna diversity under tropical and temperate conditions. Faunal responses to agricultural practices in northern latitudes may, however, differ from those in southern latitudes due to different soil types, climatic conditions, and intensity of management. We investigated the abundance and diversity of soil fauna communities (nematodes, microarthropods, enchytraeids and earthworms) in a boreal sandy soil in replicated organically and conventionally cultivated field blocks that simulated cultivation in a cereal farm and in a forage producing dairy farm. In addition to traditional methods, we investigated nematode diversity using DNA metabarcoding. The results show that organic production system did not unequivocally result in higher abundance and diversity of soil fauna compared with conventional production systems, neither in the cereal nor the dairy farming type. Instead, abundances of all soil fauna groups were typically higher in the dairy than in the cereal farming type irrespective of production system. This holds up for all functional groups of nematodes except omnivores, all four orders of Acari present, two out of the six families of Collembola, the total number of enchytraeids and density of earthworms. Nematode diversity, measured as average ZOTU number, was in conventionally cultivated cereal farming type an order of magnitude lower than in other production and farming type combinations. Of the various differences between farming types, the crop species was the most important one as it defines the management practice and thus the soil conditions where soil biota lives. Our findings underline that when comparing soil faunal communities under organic and conventional cultivation, the differences between farming types need to be considered in addition to the production system as they can have an overriding importance across the food web. © 2023 The Authors
Author keywords
Arable soil; Dairy production; Farming systems; Organic farming; Soil organisms